Advokasi dan Penyuluhan Bahaya Judi Online Bagi Masyarakat Dalam Meningkatkan Kesadaran dan Pengurangan Dampak Negatif di Baadia Baubau - Ardiansyah Ardiansyah; Iswan Iswan; Rois Rois; Basrinang Basrinang (Institut Teknologi dan Bisnis Semarang, 2023)
Background: Online gambling has become an increasing social problem in Indonesia, affecting various levels of society, especially among the younger generation. This phenomenon has widespread negative impacts, ranging from psychological, economic, to social aspects. Therefore, it is important to carry out educational and preventive efforts so that society can better understand the dangers posed by online gambling.Objective: This study aims to provide advocacy and education about the dangers of online gambling to the public through an education and information-based approach. Through this method, it is expected that society will raise awareness and understand the risks associated with online gambling behavior.Methods: This activity involves a series of programs, including counseling, group discussions, and the distribution of educational materials that cover information about the negative impacts of online gambling. The program also provides explanations about the importance of prevention through self-control and community empowerment so that they can be more alert to the potential dangers of online gambling.Results: The results of this activity show that the public is becoming more aware of the dangers of online gambling and the importance of prevention. In addition, people also understand the importance of self-control in avoiding involvement in online gambling. This program has a positive impact in increasing public understanding and awareness of this issue.Implications: Education and advocacy efforts on the dangers of online gambling need to continue to create a society that is more aware and protected from the negative impacts of online gambling.